Vietnamese EFL teachers’ cultural integration in business English classes: an ecological perspective - Pham Thi Minh Thuy; Truong Minh Hoa (Institute of Advanced Engineering and Science, 2026)
Cultural integration in English as a Foreign Language (EFL) instruction has become an important focus in Vietnamese universities, particularly in business and finance programs preparing students to navigate intercultural communication in global professional environments. While existing research has explored how language teachers include cultural elements in their instruction, limited attention has been given to understanding how these practices are shaped by the complex ecological systems where personal beliefs, institutional structures, resources, and sociocultural conditions interact dynamically. Addressing this gap, the present study investigates how EFL teachers at a Vietnamese public university integrate cultural content into their instruction. Guided by an ecological framework, the research employed a sequential mixed-methods design, collecting data through 67 questionnaires and 10 semi-structured interviews. Findings indicate that teachers prioritized international and target cultures, while local Vietnamese cultural content was largely underrepresented. Though teachers expressed strong commitment to fostering students’ intercultural competence for international business communication, their pedagogical practices were constrained by ecological factors like limited instructional time, rigid curricula, and a lack of localized, business-relevant resources. In response, several teachers leveraged personal agency and digital tools to adapt cultural content despite structural limitations. The study highlights the need for ecologically responsive cultural instruction in Business English classrooms.